The Role Promotion and Location On Purchase Decisions - Rusdi Walinono, Andi (Journal of Management, 2023)
The purpose of this study is to see how promotion and location affect purchasing decisions at Café Andju Pangkajene Regency. According to the findings of this study, promotion and location have a partially significant effect on purchase decisions at Café Andju Pangkajene Regency. At Café Andju Pangkajene Regency, promotion and location both have a big impact on purchasing decisions.